THE COMPLEX ESTIMATION OF ECOLOGICAL STATE OF GEOLOGICAL ENVIRONMENT OF FRONTIER TERRITORIES - SANINA, I. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2006)
Complex modern ecological and geological conditions, non-uniform natural conditions and significant technogeny loading have caused necessity of performance of an estimation of an ecological condition of geological environment. Generalization of a plenty of the saved information have enabled to define the tasks and criterion of an estimation of an ecological condition of geological environment of boundary territories. The analysis facts has allowed to execute an estimation of an ecological condition of geological environment of frontier territories. The executed researches of an ecological condition of geological environment of territory of frontier areas allow to define negative changes of geological environment and at a modern level to make conclusions about directions of ecological monitoring of geological environment and to develop the recommendations of its improvement.